1995
DOI: 10.1111/j.1365-2249.1995.tb03477.x
|View full text |Cite
|
Sign up to set email alerts
|

Lack of cytotoxic activity against Mycobacterium leprae 65-kD heat shock protein (hsp) in multibacillary leprosy patients

Abstract: SUMMARYCytotoxic T cells play an important role in host defence mechanisms, as well as in the immunopathology of leprosy. In this study, we evaluated whether Mycobacterium leprae hspl8, hsp65 and Myco. tuberculosis hsp7l could induce cytotoxic T cell activity against autologous macrophages pulsed with these hsp. Paucibacillary (PB) patients and normal controls generated more effector cells than multibacillary (MB) patients with all three hsp tested. There was no crossreactivity between any of the hsp tested. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 47 publications
(22 reference statements)
1
2
0
Order By: Relevance
“…Here we observed that MDR-and S-TB patients failed to induce degranulation of CD8 ϩ cells and to evoke a CTL response, likely due to the high Th2 profile induced in CD4 ϩ and CD8 ϩ cells from these patients. In line with this, a gradual loss of CD8-mediated CTL activity against autologous H37Rv-pulsed macrophages dependent on IL-10 production has been observed in patients with active S-TB (10-12), and modulation of Mycobacterium leprae Hsp65-induced CTL activity by IL-10 and IL-4 has also been observed in leprosy patients (11). In addition, IL-4 leads to development of a CD8 ϩ T-cell subset that fails to upregulate granzyme B, a potent apoptosis-inducing protease of CTLs (44).…”
Section: Discussionsupporting
confidence: 56%
“…Here we observed that MDR-and S-TB patients failed to induce degranulation of CD8 ϩ cells and to evoke a CTL response, likely due to the high Th2 profile induced in CD4 ϩ and CD8 ϩ cells from these patients. In line with this, a gradual loss of CD8-mediated CTL activity against autologous H37Rv-pulsed macrophages dependent on IL-10 production has been observed in patients with active S-TB (10-12), and modulation of Mycobacterium leprae Hsp65-induced CTL activity by IL-10 and IL-4 has also been observed in leprosy patients (11). In addition, IL-4 leads to development of a CD8 ϩ T-cell subset that fails to upregulate granzyme B, a potent apoptosis-inducing protease of CTLs (44).…”
Section: Discussionsupporting
confidence: 56%
“…In previous studies, we, as well as others [10–12], have shown that whole M. leprae and M. leprae recombinant proteins were able to induce cytotoxic activity of T lymphocytes from patients with leprosy and from BCG‐vaccinated individuals against autologous macrophages that present M. leprae antigens. It is well known that cytokines can regulate most aspects of immune function.…”
Section: Introductionmentioning
confidence: 73%
“…The bacterial Hsps might modulate immunity by rapidly and directly increasing cytokine production in macrophages. T cells reacting to Hsp65 appear to play an important role in the control of M. leprae infection (de la Barrera et al, 1995). Hsp65 directly activates monocytes during mycobacterial infection.…”
Section: Hsps As Antigens In M Tuberculosismentioning
confidence: 99%